A randomized study comparing different doses of superparamagnetic iron oxide tracer for sentinel lymph node biopsy in breast cancer: The SUNRISE study. Issue 12 (December 2020) - Rubio, Isabel T.; Rodriguez-Revuelto, Roberto; Espinosa-Bravo, Martin; Siso, Christian; Rivero, Joaquin; Esgueva, Antonio
Abstract: Introduction: The non-radioactive method that uses the magnetic tracer (SPIO/Sienna) has shown to be a feasible technique for the SLN detection in breast cancer patients. The aim of this study is to assess the efficacy of different doses of a new magnetic tracer Sienna XP (Magtrace) compared to Tc-99 m and to evaluate its non-inferiority. Methods: Patients diagnosed with early-stage breast cancer cT1-3 N0, from October 2016 to August 2018 were eligible and consecutively randomized to three different doses of new SPIO used: group 1 (1 mL), group 2 (1.5 mL) and group 3 (2 mL). Results: A total of 135 patients were included in the study, 45 in each group. Detection of SLNs with the three doses of Sienna XP (1 mL, 1.5 mL and 2 mL) showed non-inferior rates compared to the conventional technique with radiotracer (p = 0.654). Concordance by patients with SLN positive was 100% for all groups. 83 (70.3%) patients reported skin staining at one month postoperatively, significantly lower in group 1 (p = 0.042). At 6 months follow up, group 1 remains with significantly lower skin discoloration (p = 0, 01). In multivariate analysis, dose of 2 mL showed statistically significant for the skin staining. The majority of patients (70%) felt that skin discoloration does not represent a problem. Conclusion: The use of the Sienna XP magnetic tracer at 1 mL is not inferior to higher doses of magnetic tracer neither is inferior to radiotracer. 1 mL of magnetic tracer resulted in significantly less skin discoloration compared to higher doses.